Opportunistic scheduling for wireless networks - Zhang, Zhi, author; Chong, Edwin Kah Pin, author (Colorado State University. Libraries, 2006)
We consider the problem of downlink scheduling for multi-user OFDM (Orthogonal Frequency Division Multiplexing) systems. We derive optimal scheduling policies under three QoS/fairness constraints -- temporal fairness, utilitarian fairness, and minimum-performance guarantees. To calculate these optimal policies, we interpret the problem as a maximal bipartite matching problem. To solve this problem, we apply the modified Hungarian algorithm and a practical suboptimal algorithm. The simulation results show that our schemes achieve significant improvement in system performance compared with a non-opportunistic scheme.
Opportunistic downlink scheduling for multiuser OFDM systems
Opportunistic downlink scheduling for multiuser orthogonal frequency division multiplexing systems
Keywords: wireless multimedia networks; OFDM systems; orthogonal frequency division multiplexing systems; optimal opportunistic policy; opportunistic scheduling